2021
DOI: 10.1029/2021jc017308
|View full text |Cite
|
Sign up to set email alerts
|

Linking AMOC Variations With the Multidecadal Seesaw in Tropical Cyclone Activity Between Eastern North Pacific and Atlantic

Abstract: Tropical cyclone (TC) over the North Atlantic is an important extreme weather event, causing great social and economic damages to the American coastal regions. In this study, we find that the North Atlantic TC activity (genesis frequency and accumulated cyclone energy) has significant multidecadal variability, which exhibits an out‐of‐phase relationship with that over the eastern North Pacific, referring to as the inter‐basin seesaw in TC activity. By using five indicators of the Atlantic Meridional Overturnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Zhang et al (2022) found that a NAO positive phase promotes TC genesis frequency in the North Pacific. Conversely, several authors described a decrease in TC genesis in the North Pacific when AMO is in a positive phase (Gong et al, 2021;Patricola et al, 2016;Wang et al, 2022).…”
Section: Influence Of El Niño-southern Oscillation and Tropical Cyclo...mentioning
confidence: 99%
“…Zhang et al (2022) found that a NAO positive phase promotes TC genesis frequency in the North Pacific. Conversely, several authors described a decrease in TC genesis in the North Pacific when AMO is in a positive phase (Gong et al, 2021;Patricola et al, 2016;Wang et al, 2022).…”
Section: Influence Of El Niño-southern Oscillation and Tropical Cyclo...mentioning
confidence: 99%